Systematics of south american snail-eating snakes (Serpentes, dipsadini), with the description of five new species from ecuador and peru - Arteaga, Alejando (2018)
A molecular phylogeny of the Neotropical snail-eating snakes (tribe Dipsadini) is presented including 43 (24 for the first time) of the 77 species, sampled for both nuclear and mitochondrial genes. Morphological and phylogenetic support was found for four new species of Dipsas and one of Sibon, which are described here based on their unique combination of molecular, meristic, and color pattern characteristics. Sibynomorphus is designated as a junior subjective synonym of Dipsas. Dipsas latifrontalis and D. palmeri are resurrected from the synonymy of D. peruana. Dipsas latifasciata is transferred from the synonymy of D. peruana to the synonymy of D. palmeri. A new name, D. jamespetersi, is erected for the taxon currently known as Sibynomorphus petersi. Re-descriptions of D. latifrontalis and D. peruana are presented, as well as the first photographic voucher of an adult specimen of D. latifrontalis, along with photographs of all known Ecuadorian Dipsadini species. The first country record of D. variegata in Ecuador is provided and D. oligozonata removed from the list of Peruvian herpetofauna. With these changes, the number of Dipsadini reported in Ecuador increases to 22, 18 species of Dipsas and four of Sibon. © 2018, Pensoft Publishers. All rights reserved.